The San Diego Dialogue: Reshaping the San Diego region - Karen Christensen; Jane Rongerude (University of California, Institute of Urban and Regional Development (IURD), 2004)
Since 1995, the James Irvine Foundation has invested more than 11 million to support the growth and development of CRIs throughout the state nonprofit organizations that engage key players from business, environmental, and a variety of other advocacy groups with players from local governments and public agencies to create improvements in their regions. CRIs work on issues ranging across transportation, land use, housing, and economic development. They work in a variety of ways from developing legislation to media campaigns to practical work on particular projects. All are directed at building civic capacity and filling in gaps where government does not or cannot act. Some CRIs have been in place for years; others are more recently formed. They represent experiments in regional governance. The Irvine Foundation tapped a team of Berkeley faculty to perform an assessment of the CRIs so the foundation could target its resources in order to make them effective and sustainable over time and assist them in producing valuable outcomes for their regions. Together the team published case studies of four major CRIs the Bay Area Alliance for Sustainable Communities, Joint Venture: Silicon Valley, the San Diego Dialogue and the Sierra Business Council as well as an analysis of regional workforce development collaboratives in California. Professor Christensen's analysis of the San Diego Dialogue an organization that promotes civic discussion on the San Diego region's future revealed that a major element of its success was its former executive director, whose oneon-one political skills bridged the ideas and the elite networks that ultimately amplified the discourse, generating new civic knowledge and shaping the regional agenda. The Dialogue is best known for its cross-border research, which led to the installation of a rapid commuter lane for frequent border crossers. Their key finding that 96% of border crossings are made by frequent crossers demonstrated that the region is a bi-national economy and changed the way the US/Mexico border was perceived. The new outlook also provided a framework for talking about other bi-national issues such as water, energy, healthcare, manufacturing and ports of entry. Nevertheless, because the model is networkdriven and depended heavily on one person facilitating the agenda, the question remains whether the fruitful connections and successful outcomes for the region can be sustained.
Keywords: 330